An International Collaborative Assay of Factor VIII Clotting Activity - Barrowcliffe, T W; Kirkwood, T B L (Thrombosis and Haemostasis, 1978)
An International Collaborative Study was organised to replace the first International Standard for factor VIII. A freeze-dried concentrate, 73/552, and a freeze-dried plasma, 75/510, were assayed against the International Standard, and also compared to fresh normal plasma and local standards.In assays of the concentrate 73/552 against the first I.S. the mean potency was 1.14 i.u./ ampoule and there was no significant difference between one-stage and two-stage methods. When assayed against average fresh normal plasma, the potency was 1.05 “normal plasma units” per ampoule. It was agreed by the participants that the potency of 73/552 be regarded as the mean of these two figures, i.e. 1.10 i. u./ampoule.In assays of the freeze-dried plasma, 75/510, against the first I.S. the mean potency was 0. 68 i. u./ampoule, but the one-stage assays gave significantly higher potencies (mean 0.74 1. u./ampoule) than the two-stage assays (mean 0.59 i. u./ampoule). The same trend was also seen in the fresh normal plasmas, and in the local plasma standards. This finding has important implications for the standardisation of factor VIII.Stability studies on the concentrate 73/552 gave a predicted loss of 0.02% per year at – 20° C. All participants agreed that the material was suitable to serve as an International Standard, and at the 26th meeting of the Expert Committee on Biological Standardisation of the World Health Organization, the material in ampoules coded 73/552 was established as the 2nd International Standard for factor VIII, with a potency of 1.10 i. u./ampoule.